A classic that wasn't: Statistical Geography and paths only later taken. (April 2020) - Johnston, Ron; Jones, Kelvyn
Science is a cumulative activity, a body of knowledge sedimented in its publications, which form the foundation for further activity. Some items attract more attention than others; some are largely ignored. This paper looks at a largely overlooked book – Statistical Geography – published by three US sociologists at a time when geographers were launching their 'quantitative revolution'. There was little literature within the discipline on which that revolution could be based, and a book with that title could have been seminal. But it was not, and as a consequence – as illustrated with three examples – major issues in spatial analysis were not addressed in the revolution's early years. The paper explores why.